2013
DOI: 10.7314/apjcp.2013.14.8.4785
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Consumption and Breast Cancer Survival: A Metaanalysis of Cohort Studies

Abstract: Background and Objectives: Evidence for associations between alcohol consumption with breast cancer survival are conflicting, so we conducted the present meta-analysis. Methods: Comprehensive searches were conducted to find cohort studies that evaluated the relationship between alcohol consumption with breast cancer survival. Data were analyzed with meta-analysis software. Results: We included 25 cohort studies. The meta-analysis results showed that alcohol consumption was not associated with increased breast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 35 publications
(127 reference statements)
1
26
1
Order By: Relevance
“…The majority of authors hold that use of either tobacco or alcohol constitutes a risk factor for breast cancer, for a prognostic of a shorter survival time after a mastectomy, and for an increase in rates of tumor recurrence, based on empirical conclusions from large population studies and meta-analysis (Stefani et al, 2011;Park et al, 2012;Gou et al, 2013). However, the risk of metastasis and the status of the tumor markers associated with the use of alcohol and/or tobacco has been less studied.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of authors hold that use of either tobacco or alcohol constitutes a risk factor for breast cancer, for a prognostic of a shorter survival time after a mastectomy, and for an increase in rates of tumor recurrence, based on empirical conclusions from large population studies and meta-analysis (Stefani et al, 2011;Park et al, 2012;Gou et al, 2013). However, the risk of metastasis and the status of the tumor markers associated with the use of alcohol and/or tobacco has been less studied.…”
Section: Discussionmentioning
confidence: 99%
“…As of 2004, there was an increase in the number of individual studies and systematic reviews with meta-analysis, and they left little doubt about the association between breast cancer and the use of tobacco and/or alcohol. Alcohol consumption above all was clearly associated with this malady (de Menezes et al, 2013;Gao et al, 2013;Gou et al, 2013).…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…A recent meta-analysis of 14 cohort studies concluded that postdiagnosis alcohol consumption was not associated with breast cancer mortality, although subgroup analyses found that high intake of alcohol (> 20 g/d) was associated with higher breast cancer mortality, with a dose-response association among premenopausal women. 55 A subsequent pooled analysis of four cohort studies reported that alcohol intake of more than one drink daily was associated with a 28% increased risk of late recurrence (> 5 yr after diagnosis) (95% CI 1.01-1.62) among survivors with estrogen-receptor-positive breast cancer. 50 Overall, the results are inconclusive.…”
Section: Is There a Benefit From Quitting Smoking And Reducing Alcohomentioning
confidence: 99%
“…As a multifactorial disease, breast cancer is associated not only with environmental and hereditary factors but also dietary factors including folate, vitamin B6, vitamin B12 and alcohol (Ma et al, 2009;Gou et al, 2013;Liu et al, 2013).…”
Section: Introductionmentioning
confidence: 99%